592 Enhancing the therapeutic potential of oncolytic adenoviruses with vSENS™ technology. (9th November 2020) - Kim, Goo-Young; Son, Ji Yeon; Lee, So Jin; Jo, Sang Woo; In, Changhoon; Kim, Sang Hoon; Park, Joon Young; Kim, So-Young; Moon, Gyu-Young; Choi, Ji-Hye; Kim, Suk-Hwan; Yun, Minhyuk; et al.
Abstract : Background: Oncolytic viro-therapeutics is a promising treatment for cancer. Among the different strains of oncolytic viruses currently being developed, potent cytolytic activity, manageable safety profiles, large genomic capacity for addition of transgenes and available advanced manufacture processes make adenovirus (Ad) a great choice. 1 However, the delivery of Ad for clinical application is limited due to 1) neutralization by pre-existing neutralizing antibodies (nAb) in bloodstream and 2) receptor restricted tumor-cellular entry. 2 To overcome these limitations, we developed a novel proprietary polymer nanoparticle delivery system, so called Stability Enhanced Nano Shells (SENS™) for the delivery of Virus (vSENS). Methods: SENS™ employs proprietary an ionizable cationic lipid and biodegradable and biocompatible polymers. Following complexation with replication-incompetent adenovirus serotype 5 (Ad-vSENS) or replication-competent oncolytic adenovirus serotype 5 (OAd-vSENS), the physicochemical properties of the complexes were characterized by dynamic light scattering (DLS) and electron microscopy. The benefit of vSENS in coxsackievirus and adenovirus receptor (CAR) restricted cellular transduction of adenovirus was evaluated with Ad-vSENS in CAR negative cancer cells. Pharmacokinetic profile of OAd-vSENS was examined in mice following systemic administration to assess the protective effect of vSENS in the presence of pre-existing immunity to Adenoviral proteins. Anti-tumor efficacy was evaluated in syngeneic subcutaneous tumor mice models. The serum level of alanine aminotransferase (ALT) in mice was evaluated by blood chemistry analyzer. Results: Ad-vSENS effectively infected cancer cells in CAR-independent manner, where cancer cell-killing effects of OAd-vSENS were significantly enhanced in CAR negative cancer cells compare with those of naked OAd. When vSENS is complexed with an adenovirus, it encapsulates the virus like a shell shielding the adenovirus. Consistently, in syngeneic tumor bearing mice with pre-existing Ad immunity, longer virus blood half-life and longer survival of the mice were observed when administered with OAd-vSENS compared to naked OAd. The hepatotoxicity of OAd was greatly reduced by vSENS formulation as evidenced by the absence of acute spike in serum ALT levels typically seen after systemic administration of OAd. Conclusions: The results show the potential of vSENS as a novel platform technology for delivery of Ad to overcome challenges adeno-virotherapies face in the clinic. vSENS platform is expected to expand the efficacy of the virus from cancer patients with high CAR expression to patients with limited CAR expression often associated as the cancer progresses. The platform is likely to facilitate treatment in patients with high levels of antibodies to adenovirus by shielding the virus from neutralization and increasing the bioavailability. Ethics Approval: The study was approved by Samyang Biopharmaceuticals Institution's Ethics Board, approval number SYAU2009. References: Twumasi-Boateng K, Pettigrew JL, Kwok YYE, Bell JC, Nelson BH, Oncolytic viruses as engineering platforms for combination immunotherapy. Nat Rev Cancer 2018;18:419–322. Zheng M, Huang J, Tong A, Yang H, Oncolytic viruses for cancer therapy: barriers and recent advances. Mol Ther Oncolytics 2019;15:234–247.